Population dynamics, urbanization and environmental quality in Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The link between population dynamics, urbanization and environmental quality remains a topical issue among environmental economists and policymakers. This study assessed the relationship between population dynamics, urbanization and environmental quality in Nigeria from 1980 to 2022 using the ordinary least squares (OLS) on the framework of ARDL. The study found negative and significant impact of crude birth rate and gross domestic product per capita on environmental quality. Also, net-migration, technology and urbanization impacted positive on environmental quality. This means net-migration, technology and urbanization have a damaging effect on the environment. This implies that a policy that will curb rising crude birth rate as well as increasing influx (net migration) of persons will help in no small way in enhancing environmental quality in Nigeria. The study therefore amongst others recommends that government should regulate the technique of production adopted in Nigeria to be sure it is environmentally friendly.
Keywords: Population; Growth; urbanization; Institution and Environment Quality JEL; J11; O44; Q53; Q43 and Q56